2019
DOI: 10.1128/mcb.00210-19
|View full text |Cite
|
Sign up to set email alerts
|

During Adipocyte Remodeling, Lipid Droplet Configurations Regulate Insulin Sensitivity through F-Actin and G-Actin Reorganization

Abstract: Adipocytes have unique morphological traits in insulin sensitivity control. However, how the appearance of adipocytes can determine insulin sensitivity has not been understood. Here, we demonstrate that actin cytoskeleton reorganization upon lipid droplet (LD) configurations in adipocytes plays important roles in insulin-dependent glucose uptake by regulating GLUT4 trafficking. Compared to white adipocytes, brown/beige adipocytes with multilocular LDs exhibited well-developed filamentous actin (F-actin) struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 56 publications
2
36
2
Order By: Relevance
“…Our results are consistent with a recent study that demonstrated correlations between adipocyte size, actin cytoskeletal complexity, and insulin resistance [ 65 ]. These results differ from another study, however, in which it was reported that larger adipocytes with functional declines had reduced actin polymerization [ 66 ]. Interestingly, chemical compounds that interfere with actin cytoskeletal dynamics either by stabilizing actin polymerization or inhibiting polymerization have negative impacts on insulin-stimulated glucose uptake in adipocytes, apparently by disrupting glucose transporter type 4 (GLUT4) vesicular trafficking [ 67 , 68 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are consistent with a recent study that demonstrated correlations between adipocyte size, actin cytoskeletal complexity, and insulin resistance [ 65 ]. These results differ from another study, however, in which it was reported that larger adipocytes with functional declines had reduced actin polymerization [ 66 ]. Interestingly, chemical compounds that interfere with actin cytoskeletal dynamics either by stabilizing actin polymerization or inhibiting polymerization have negative impacts on insulin-stimulated glucose uptake in adipocytes, apparently by disrupting glucose transporter type 4 (GLUT4) vesicular trafficking [ 67 , 68 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Reversed feeding correspondingly restored cell size, insulin response, expression of F-actin, and its regulatory proteins [143]. Although this study indicated the critical role of actin in adipocyte remodeling, the effect of cytoskeleton on the structure of adipocytes is quite contrary to the findings in other articles [138,144]. Considering that studies listed above used different animal models and/or analyzed different AT depots, different signaling pathways (Akt pathway, Wnt-GSK3β pathway, etc.)…”
Section: Development Of "Supersized" Lipid Dropletcontrasting
confidence: 63%
“…F-Actin is a filamentous polymer composed of multiple globular actin (G-actin) subunits. The dynamics of the intracellular ratio between F-actin and G-actin are vital for actin remodeling [ 26 , 27 ]. In our experiment, rhodamine phalloidin was used to specifically labeled F-actin, instead of combining it with G-actin.…”
Section: Discussionmentioning
confidence: 99%